• 1.(2x-1)^2-4(x-2)(x+2)=0
    2.(3a-b)^2-(3a+b)^2
    3.(a+(b-c))
    1.Решите уравнение.
    2,3.Раскройте скобки.

Ответы 1

  • 1. (2x-1)^2-4(x-2)(x+2)=0 \\ 4x^2-4x+1-4(x^2-4)=0 \\ 4x^2-4x+1-4x^2+16=0 \\ -4x+17=0 \\ 4x=17 \\ x= \frac{17}{4}=4,25 2. (3a-b)^2-(3a+b)^2=9a^2-6ab+b^2-(9a^2+6ab+b^2)= 9a^2-6ab+b^2-9a^2-6ab-b^2=-12ab3. a+(b-c)=a+b-c
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years